Metallic Nanobrushes Made using Ambient Droplet Sprays. Issue 11 (20th January 2016) - Sarkar, Depanjan; Mahitha, Maheswari Kavirajan; Som, Anirban; Li, Anyin; Wleklinski, Michael; Cooks, Robert Graham; Pradeep, Thalappil
Abstract : An ambient solution‐state method for making uniform nanobrushes composed of oriented 1D silver nanowires (NWs) with aspect ratios of 10 2 –10 4 is reported. These structures are grown over cm 2 areas on conducting surfaces. Assemblies of NWs form uniform nanobrush structures, which can capture micrometer‐sized objects, such as bacteria and particulate matter. Variation in composition produces unique structures with catalytic properties.